2014
DOI: 10.1155/2014/894710
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Nitrogen Use Efficiency in Inbred Progenies of Tropical Maize Based on Multivariate Diallel Analysis

Abstract: The objective of our study was to characterize and determine the patterns of genetic control in relation to tolerance and efficiency of nitrogen use by means of a complete diallel cross involving contrasting inbred progenies of tropical maize based on a univariate approach within the perspective of a multivariate mixed model. Eleven progenies, previously classified regarding the tolerance and responsiveness to nitrogen, were crossed in a complete diallel cross. Fifty-five hybrids were obtained. The hybrids and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
0
1
Order By: Relevance
“…Considering that the difference in grain yield between the two environments was approximately 548 kg ha -1 and that the difference of N applied was 100 kg, the mean response of kg of grains produced per kg of N applied was approximately 5.5 kg. These results are a magn itude lower than those found by Guedes et al (2014), who found a mean response of 17 and 24 kg of grains per kg of N applied in maize crops, respectively. However, these results can be attributed to low water availability and stressful factors present in the off-season, which reduces the potential of the crop response to N application.…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…Considering that the difference in grain yield between the two environments was approximately 548 kg ha -1 and that the difference of N applied was 100 kg, the mean response of kg of grains produced per kg of N applied was approximately 5.5 kg. These results are a magn itude lower than those found by Guedes et al (2014), who found a mean response of 17 and 24 kg of grains per kg of N applied in maize crops, respectively. However, these results can be attributed to low water availability and stressful factors present in the off-season, which reduces the potential of the crop response to N application.…”
Section: Resultscontrasting
confidence: 77%
“…There was a significant effect for top-crosses, TCt1, TCt2, GCA, SCA and controls, which indicates the existence of genetic variability. Cancellier, Afférri, Carvalho, Dotto, and Leão (2011) and Guedes et al (2014) found similar results.…”
Section: Resultssupporting
confidence: 58%